PENGARUH SELF EFFICACY DAN JOB BURNOUT PADA PRODUKTIVITAS KERJA KARYAWAN PT. NASMOCO BAHANA MOTOR (NASMOCO BANTUL) - Agus Mulyono,; Danang Sunyoto, (Journal of Innovation Research and Knowledge, 2024)
This study aims to analyze the effect of self-efficacy and job burnout on employee work productivity at PT. Nasmoco Bahana Motor (Nasmoco Bantul). Self-efficacy refers to employees' belief in their ability to complete tasks, while job burnout refers to emotional and physical stress due to workload. Work productivity is measured based on employees' ability to achieve predetermined work targets. The research method uses a quantitative approach with data collection through questionnaires distributed to employees. Data analysis was carried out using multiple linear regression to test the relationship between self-efficacy, job burnout, and work productivity. The results showed that self-efficacy had a positive and significant effect on work productivity, meaning that employees with higher levels of self-efficacy tend to be more productive. Job burnout also had a positive and significant effect, indicating that in certain situations, high work pressure can encourage increased productivity